Catalytic effect of sandwich-like Ti3C2/TiO2(A)-C on hydrogen storage performance of MgH2. (24th December 2019) - Gao, Haiguang; Liu, Yana; Zhu, Yunfeng; Zhang, Jiguang; Li, Liquan
Abstract: A sandwich-like Ti3 C2 /TiO2 (A)-C prepared through a facile gas–solid method was doped into MgH2 by ball milling. Ti3 C2 /TiO2 (A)-C shows a far superior catalytic effect on the hydrogen storage of MgH2 than individual Ti3 C2 or TiO2 (A)-C, assigning as a synergistic catalysis between Ti3 C2 and TiO2 (A)-C. For example, the peak dehydrogenation temperature of MgH2 -5 wt% Ti3 C2 /TiO2 (A)-C is reduced to 308 °C, much lower than that of MgH2 -5 wt% Ti3 C2 (340 °C) or MgH2 -5 wt% TiO2 (A)-C (356 °C). After dehydrogenation, the dehydrogenated MgH2 -5 wt% Ti3 C2 /TiO2 (A)-C can uptake approximately 4 wt% of hydrogen within 800 s at 125 °C, while for the dehydrogenated MgH2 -5 wt% Ti3 C2 and MgH2 -5 wt% TiO2 (A)-C, only 3 wt% and 2.65 wt% hydrogen content can be obtained, respectively. Besides this, MgH2 -5 wt% Ti3 C2 /TiO2 (A)-C exhibits the lowest apparent activation energies (42.32 kJ mol −1 H2 for the hydrogen absorption and 77.69 kJ mol −1 H2 for the hydrogen desorption), which can explain the excellent hydrogen ab/desorption kinetic properties. The synergetic effects between the special layered structure and multiple valence titanium compounds (Ti 4+, Ti 3+, Ti 2+, Ti 0 ) verified by the x-ray photoelectron spectroscopy results are responsible for the catalytic mechanism on the hydrogen storage of MgH2 . This study also supplies innovative insights into designing high efficiency MXene derivative catalysts in hydrogen storage.